Pengaruh Kepuasan Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada CV Karya Taruna Teknik Depok Jawa Barat - Wisnugroho Aji; Sheila Ardilla Yughi (Journal on Education, 2024)
This research aims to find out the impact of job satisfaction and workload on employee performance on CV. The research method used is a quantitative method with a sample of 85 respondents. Based on the results of the research on the first hypothesis obtained t count value > t table or (6,749 > 1,98896) It is also reinforced with the value of Sig. < 0,05 or (0,000 < 0,05) so that partially variable Job satisfaction there is a significant influence on Employee Performance on the CV. The work of Taruna Technical Depok Java West. On the test results on the second hypotheses obtains a value of t count > t Table or (7,899 > 1, 98896) This is also strengthened with a Sig. value < 0.05 or (0.000< 0,05). Thus partially the workload variable has a significant impact on the performance of Employees on CV.